The inhibitory avoidance discrimination task to investigate accuracy of memory - Atucha, Erika; Roozendaal, Benno (Frontiers in Behavioral Neuroscience, 2015)
The present study was aimed at developing a new inhibitory avoidance task, based on training and/or testing rats in multiple contexts, to investigate accuracy of memory. In the first experiment, male Sprague-Dawley rats were given footshock in an inhibitory avoidance apparatus and, 48 h later, retention latencies of each rat were assessed in the training apparatus (Shock box) as well as in a novel, contextually modified, apparatus. Retention latencies in the Shock box were significantly longer than those in the Novel box, indicating accurate memory of the training context. When the noradrenergic stimulant yohimbine (0.3 mg/kg, sc) was administered after the training, 48-h retention latencies in the Shock box, but not Novel box, were increased, indicating that the noradrenergic activation enhanced memory of the training experience without reducing memory accuracy. In the second experiment, rats were trained on an inhibitory avoidance discrimination task: They were first trained in an inhibitory avoidance apparatus without footshock (Non-Shock box), followed 1 min later by footshock training in a contextually modified apparatus (Shock box). Forty-eight-hour retention latencies in the Shock and Non-Shock boxes did not differ from each other but were both significantly longer than those in a Novel box, indicating that rats remembered the two training contexts but did not have episodic-like memory of the association of footshock with the correct training context. When the interval between the two training episodes was increased to 2 min, rats showed accurate memory of the association of footshock with the training context. Yohimbine administered after the training also enhanced rats’ ability to remember in which training context they had received actual footshock. These findings indicate that the inhibitory avoidance discrimination task is a novel variant of the well-established inhibitory avoidance task suitable to investigate accuracy of memory.